The Effect of Benefits Gained from Leisure Activities on Entrepreneurship and Academic Hopelessness - Anıl Siyahtaş; Veli Ozan Çakır (Journal of Educational Issues, 2024)
The importance of the benefits that individuals get from the activities they participate in their leisure is increasing day by day. It is known that the benefits gained are reflected positively in many aspects of the individual’s life. From this point of view, this study aimed to examine the effect of the benefits obtained by university students in their leisure on the prediction of entrepreneurship and academic hopelessness. The study group of the research consisted of a total of 457 students, 247 males and 210 females, selected by easy sampling method, and studying at Istanbul University-Cerrahpaşa Faculty of Sports Sciences. In addition to the personal information form, Leisure Benefit Scale (LBS) developed by Ho (2008) and adapted into Turkish by Akgül et al. (2018); Entrepreneurship Scale (ES) developed by Yılmaz and Sünbül (2009) and Academic Hopelessness Scale (AHS) developed by Gökalp and Soykan (2020) were used as data collection tools. The normality distribution of the data was decided according to the skewness and kurtosis values. After the data showed normal distribution, t-test, Pearson Correlation test, Multiple Regression analysis were performed in the analysis. As a result, while there were differences between university students’ leisure benefits and academic hopelessness according to their gender, a significant relationship was found between leisure benefits and entrepreneurship and academic hopelessness. In this context, it was concluded that social benefit from leisure benefits was a significant predictor of entrepreneurship and academic hopelessness.